Nanoscale tetragonal-phase barium titanate and confinement preparation method thereof
By using a microchannel reactor for domain-limited mixing and hydrothermal reaction in the preparation of barium titanate, the problem of difficult control of particle size and phase structure stability in the prior art is solved, and efficient preparation of nano-scale tetragonal phase barium titanate is achieved, with high controllability and industrial application value.
Patent Information
- Application Number
- CN202411864122.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
AI Technical Summary
The existing barium titanate preparation method is difficult to effectively control the particle size and phase structure stability, especially in large-scale production, which is difficult to achieve stable control, and traditional technologies are difficult to meet the needs of high-end applications for narrow particle size distribution and tetragonal phase forming stability.
A microchannel reactor was used to perform domain-limited mixing and hydrothermal reaction. Through efficient mass transfer performance and fast and uniform mixing characteristics, a high-active small-size barium titanate precursor was prepared, and a nano-scale tetragonal phase barium titanate was stably generated under mild hydrothermal reaction conditions.
The preparation of nano-scale tetragonal phase barium titanate with small size, high crystallinity, high particle size and high tetragonal phase purity has been achieved, with high controllability and industrial potential, significantly improving the overall performance of the material.
Smart Images

Figure CN119637933A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of barium titanate preparation, and specifically relates to nano-scale tetragonal barium titanate and a confined preparation method thereof. Background Art
[0002] Existing methods for preparing barium titanate, such as the solid phase method, are mature, but it is difficult to effectively control the particle size and phase structure stability; although wet methods such as the hydrothermal method and the sol-gel method improve the uniformity of the particles, it is difficult to achieve stable control during large-scale production. For example, in the related technology, tetrabutyl titanate is used as the titanium source, and the solvent thermal method is adopted to increase the reaction pressure of the hydrothermal autoclave by pressurization, thereby obtaining cubic barium titanate at a lower temperature, and then promoting the formation of the tetragonal phase by calcination. The average particle size of the prepared tetragonal barium titanate is 160-220nm, and the specific surface area is 4.5-8m 2 / g. In order to achieve the tetragonal phase, calcination treatment is required at a higher temperature, which increases the complexity of the process and makes it difficult to ensure consistency in large-scale production.
[0003] As the market demand for thinner and more multilayered dielectric layers in multilayer ceramic capacitors (MLCCs) increases, the narrow particle size distribution and stability of tetragonal phase formation of barium titanate particles are particularly important. Traditional technologies have been unable to meet the needs of high-end applications. The existing technology urgently needs a mild and controllable preparation method that can achieve a small size and stable tetragonal phase structure while ensuring a narrow particle size distribution. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a nano-scale tetragonal barium titanate and a confined preparation method thereof, which can efficiently and stably prepare nano-scale tetragonal barium titanate with small size, high crystallinity, high particle size uniformity and high tetragonal phase purity.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing nano-scale tetragonal barium titanate by confinement, comprising the following steps:
[0007] The barium titanium salt solution and the precipitant solution are pumped into a mixing reactor of a microchannel reactor for confined mixing, and the obtained mixed slurry is aged to obtain a barium titanate precursor;
[0008] The flow rates of the barium titanium salt solution and the precipitant solution are independently 20 to 70 mL / min;
[0009] The barium titanate precursor, the barium source and water are mixed to carry out a hydrothermal reaction to obtain nano-scale tetragonal barium titanate.
[0010] Preferably, the molar ratio of titanium to the precipitant in the barium titanium salt is 1:1-20.
[0011] Preferably, the precipitant is sodium hydroxide.
[0012] Preferably, the barium titanium salt solution and the precipitant solution enter the mixing reactor through the microchannel of the microchannel reactor; the number of fluid layers in the microchannel is 24 to 60, the thickness of a single fluid layer is 100 μm, and the width of a single fluid layer is 105 μm, 210 μm or 400 μm; the fluid layers of the microchannel are evenly distributed at an injection angle of 30° to form an annular structure, and the center of the annular structure is a circular through hole, namely the mixing reactor.
[0013] Preferably, the cross-sectional area of the single fluid layer is 1.05×10 -2 mm 2 , 2.1×10 -2 mm 2 or 4.0×10 - 2 mm 2 .
[0014] Preferably, before the confined mixing, the method further comprises: preheating the barium titanium salt solution and the precipitant solution; the preheating temperature is 70-80°C.
[0015] Preferably, the temperature of the hydrothermal reaction is 200-250° C., and the insulation time is 24-100 h.
[0016] Preferably, the molar ratio of barium in the barium source to titanium in the barium titanate precursor is 1 to 3:1.
[0017] Preferably, the aging temperature is 70-80° C., and the insulation time is 30-60 min.
[0018] The present invention also provides nano-scale tetragonal barium titanate prepared by the confined preparation method described in the above technical solution, wherein the average particle size of the nano-scale tetragonal barium titanate is ≤100nm, the crystallinity is ≥65%, and the tetragonal phase content is 100%.
[0019] The invention provides a confined preparation method of nano-scale tetragonal barium titanate, comprising the following steps: pumping a barium titanium salt solution and a precipitant solution into a mixing reactor of a microchannel reactor for confined mixing, aging the obtained mixed slurry to obtain a barium titanate precursor; the flow rates of the barium titanium salt solution and the precipitant solution are independently 20 to 70 mL / min; mixing the barium titanate precursor, a barium source and water for hydrothermal reaction to obtain nano-scale tetragonal barium titanate.
[0020] The present invention can achieve uniform mixing and nucleation of reactants in a relatively short time through the efficient mixing and mass transfer performance of the microchannel reactor, thereby avoiding the problems of uneven particle size and agglomeration. The microchannel reactor can prepare a barium titanate precursor with small particle size, uniform distribution and high reactivity by accurately controlling the reaction conditions, providing an ideal raw material for the subsequent hydrothermal reaction, and finally obtaining barium titanate particles with small nanometer size, high particle size uniformity, high crystallinity and narrow particle size distribution. Moreover, tetragonal barium titanate can be stably generated under mild hydrothermal reaction conditions. In addition, the precise flow rate control and rapid mixing characteristics of the microchannel reactor greatly improve the controllability of the reaction, make the process parameters easier to adjust and optimize, and have better repeatability, shorter reaction time, higher process stability, high efficiency, energy saving, and suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 TEM spectrum and diffraction pattern of the barium titanate precursor in Example 1;
[0022] Figure 2 This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 1;
[0023] Figure 3 TEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 1, wherein the scale of (a) is 200 nm and the scale of (b) is 5 nm;
[0024] Figure 4 This is a SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 1;
[0025] Figure 5 This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 2;
[0026] Figure 6 This is a SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 2;
[0027] Figure 7 This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 3;
[0028] Figure 8 This is a SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 3;
[0029] Fig. 9 This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 4;
[0030] Fig.10 This is a SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 4;
[0031] Fig.11This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 5;
[0032] Fig.12 This is a SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 5;
[0033] Fig.13 This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 6;
[0034] Fig.14 This is a SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 6;
[0035] Fig.15 This is the XRD pattern of barium titanate prepared in Comparative Example 1;
[0036] Fig.16 This is the SEM spectrum of barium titanate prepared in Comparative Example 1. DETAILED DESCRIPTION
[0037] The present invention provides a method for preparing nano-scale tetragonal barium titanate by confinement, comprising the following steps:
[0038] The barium titanium salt solution and the precipitant solution are pumped into a mixing reactor of a microchannel reactor for confined mixing, and the obtained mixed slurry is aged to obtain a barium titanate precursor;
[0039] The flow rates of the barium titanium salt solution and the precipitant solution are independently 20 to 70 mL / min;
[0040] The barium titanate precursor, the barium source and water are mixed to carry out a hydrothermal reaction to obtain nano-scale tetragonal barium titanate.
[0041] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0042] The invention pumps a barium titanium salt solution and a precipitant solution into a mixing reactor of a microchannel reactor for confined mixing, and ages the obtained mixed slurry to obtain a barium titanate precursor.
[0043] As an embodiment, the preparation method of the barium titanium salt solution is: adding barium salt to a titanium salt solution to obtain a barium titanium salt solution; the titanium salt is titanium tetrachloride; the barium salt is barium chloride; the concentration of the titanium salt in the barium titanium salt solution is 0.1-0.5 mol / L, and in a specific embodiment, it is 0.2-0.5 mol / L; the total concentration of the barium salt and the titanium salt in the barium titanium salt solution is 0.3-1.0 mol / L, and in a specific embodiment, it is 0.5-0.75 mol / L; the molar ratio of the barium salt to the titanium salt in the barium titanium salt solution is 1-3:1, and in a specific embodiment, it is 1.5-2:1.
[0044] As an embodiment, the precipitant is sodium hydroxide.
[0045] As an implementation mode, the molar ratio of titanium to precipitant in the barium titanium salt is 1:1-20, and in a specific embodiment, it is 1:2.5-14; the equipment used for pumping is a metering pump.
[0046] As an embodiment, before the confined mixing, the method further includes: preheating the barium titanium salt solution and the precipitant solution; the preheating temperature is 70 to 80° C., and is 80° C. in a specific embodiment; and the preheating is water bath heating.
[0047] As an embodiment, the barium titanium salt solution and the precipitant solution enter the mixing reactor through the microchannel of the microchannel reactor; the number of fluid layers in the microchannel is 24 to 60, the thickness of a single fluid layer is 100 μm, and the width of a single fluid layer is 105 μm, 210 μm or 400 μm; the fluid layers of the microchannel are evenly distributed at an injection angle of 30° to form an annular structure, and the center of the annular structure is a circular through hole, namely the mixing reactor.
[0048] As an embodiment, the cross-sectional area of the single fluid layer is 1.05×10 -2 mm 2 , 2.1×10 -2 mm 2 or 4.0×10 -2 mm 2 .
[0049] As an embodiment, the flow rate of the barium titanium salt solution is 20 to 70 mL / min, and in specific embodiments, it is 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min or 70 mL / min.
[0050] As an embodiment, the flow rate of the precipitant solution is 20 to 70 mL / min, and in specific embodiments, it is 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min or 70 mL / min.
[0051] As an embodiment, the flow rate ratio of the barium titanium salt solution and the precipitant solution is 20-70:20-70, and in specific embodiments, it is 1:1, 7:3 or 3:7.
[0052] As an embodiment, the aging temperature is 70-80°C, 80°C in a specific embodiment, and the insulation time is 30-60min, 60min in a specific embodiment; the aging is carried out under conditions of water bath heating and stirring; the stirring rate is 200-400rpm, 250-280rpm in a specific embodiment.
[0053] As an embodiment, after the aging, the method further comprises: performing solid-liquid separation on the aged mixed slurry, and sequentially washing and filtering the obtained precipitate to obtain a barium titanate precursor.
[0054] As an embodiment, the solid-liquid separation is static sedimentation; the static sedimentation time is 5 to 36 hours, and in a specific embodiment, it is 12 to 24 hours; the washing solution is deionized water.
[0055] The high-frequency collision of small molecules in the barium titanium salt solution and the precipitant solution in the microchannel reactor enables the nucleation process to be completed rapidly, forming a small-sized precursor with high activity, which provides a highly active raw material for the subsequent hydrothermal reaction and promotes the formation of uniform-sized tetragonal barium titanate.
[0056] After obtaining the barium titanate precursor, the present invention mixes the barium titanate precursor, a barium source and water to perform a hydrothermal reaction to obtain nano-scale tetragonal barium titanate.
[0057] As an implementation mode, the barium source is barium hydroxide, and in a specific embodiment, it is barium hydroxide octahydrate; the molar ratio of barium in the barium source to titanium in the barium titanate precursor is 1 to 3:1, and in a specific embodiment, it is 2:1; the water is deionized water; the hydrothermal reaction is carried out in a hydrothermal kettle; the hydrothermal kettle is a polytetrafluoroethylene-lined reactor; the amount of water used is such that the volume of the material in the hydrothermal kettle accounts for 70% of the total volume of the hydrothermal kettle.
[0058] As an embodiment, the temperature of the hydrothermal reaction is 200-250° C., and in a specific embodiment, it is 200-220° C., and the insulation time is 24-100 h, and in a specific embodiment, it is 24-96 h.
[0059] As an embodiment, after the hydrothermal reaction, the method further comprises: centrifugally washing and drying the product of the hydrothermal reaction in sequence to obtain nano-scale tetragonal barium titanate.
[0060] As an embodiment, the detergent used for the centrifugal washing is an aqueous solution of glacial acetic acid, and the concentration of the aqueous solution of glacial acetic acid is 0.05 mol / L; the number of centrifugal washings is 4 to 6 times, and 6 times in the specific embodiment; the rotation speed of each centrifugal washing is 3000 to 10000 rpm, and 8000 rpm in the specific embodiment; the time of each centrifugal washing is 1 to 10 minutes, and 3 to 5 minutes in the specific embodiment.
[0061] As an implementation mode, the drying temperature is 50-100° C., and in a specific embodiment, it is 80° C.; the drying time is 24-100 h, and in a specific embodiment, it is 36 h.
[0062] The present invention also provides nano-scale tetragonal barium titanate prepared by the confined preparation method described in the above technical solution, wherein the average particle size of the nano-scale tetragonal barium titanate is ≤100nm, the crystallinity is ≥65%, and the tetragonal phase content is 100%.
[0063] As an embodiment, the average particle size of the nano-scale tetragonal barium titanate is 65 to 91 nm, and in specific embodiments, it is 65 nm, 75 nm, 76 nm, 80 nm, 82 nm, 85 nm, 87 nm or 91 nm.
[0064] As an embodiment, the crystallinity of the nano-scale tetragonal barium titanate is ≥65%, and in specific embodiments it is 65.34%, 67.78%, 67.79%, 68.14%, 68.51%, 68.60%, 68.87%, 69.23%, 69.42%, 69.84% or 71.94%.
[0065] As an implementation manner, the tetragonal phase content of the nano-scale tetragonal barium titanate is 100%.
[0066] The present invention combines a microchannel reactor with a hydrothermal method, and utilizes the microchannel reactor to have efficient mass transfer performance, and can achieve the characteristics of rapid and uniform mixing of reactants in a short time, and prepares a highly active small-sized amorphous barium titanate precursor through high-frequency collision of the molecular scale of the reactants. On this basis, through a hydrothermal reaction, the formation of nano-scale tetragonal barium titanate is promoted by a mild hydrothermal reaction. This method can not only accurately control the particle size of barium titanate particles, but also generate tetragonal barium titanate with high crystallinity and narrow particle size distribution under relatively mild conditions. In addition, the combination of a microchannel reactor and a hydrothermal method simplifies the process flow, shortens the precursor preparation time, and the prepared barium titanate powder has the advantages of small particle size, narrow particle size distribution, high crystallinity, high uniformity, and high tetragonal phase purity, and can also effectively overcome the problems of large particle size, uneven particle size distribution, poor tetragonal phase molding stability, difficult to control particle size distribution, difficult to stabilize phase structure, and complex process in the prior art. The confined domain preparation method provided by the present invention has high controllability and industrialization potential, significantly improves the overall performance of barium titanate materials, and has significant industrial application value.
[0067] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0068] Example 1
[0069] (1) Confined mixing: a 0.5 mol / L titanium tetrachloride solution was prepared and barium chloride was added to obtain a solution with a total concentration of barium salt and titanium salt of 0.75 mol / L as a barium titanium salt solution, and a 3 mol / L sodium hydroxide solution was used as a precipitant. The two solutions were heated to 80°C in a water bath, and the solution was introduced into a mixing reactor through a microchannel at a flow rate of 60 mL / min and 60 mL / min, respectively, by a metering pump for confined mixing to obtain a mixed slurry. The number of fluid layers in the microchannel was 36, the thickness of a single fluid layer was 100 μm, the width was 210 μm, and the cross-sectional area of a single fluid layer was 2.1×10 -2 mm 2 The fluid layer of the microchannel is evenly distributed at an injection angle of 30° to form a ring structure. The center of the ring structure is a circular through hole, i.e., a mixing reactor. At this time, the molar ratio of sodium hydroxide to titanium in the barium titanium salt solution is 6:1. The microchannel reactor controls the flow rate of the solution through a metering pump and quickly mixes to achieve molecular collision nucleation reaction.
[0070] (2) Slurry aging: The mixed slurry was placed in a three-necked bottle and aged for 60 min under the conditions of heating in a water bath at 80° C. and stirring at 280 rpm;
[0071] (3) Separation by precipitation and washing: After the aging is completed, the aged mixed slurry is allowed to settle for 24 hours, and after removing the supernatant, the obtained precipitate is washed and filtered with deionized water to ensure that impurities are completely removed to obtain a barium titanate precursor;
[0072] (4) Hydrothermal reaction: After the solid content of the barium titanate precursor is determined, it is placed in a 500 mL polytetrafluoroethylene-lined reactor, and barium hydroxide octahydrate is added in a molar ratio of 2:1 between barium in the barium source and titanium in the barium titanate precursor, and deionized water is added to 70% of the total volume of the polytetrafluoroethylene-lined reactor. The polytetrafluoroethylene-lined reactor is then placed in an oven at 220° C. for a hydrothermal reaction for 36 hours.
[0073] (5) Product treatment: After the hydrothermal reaction is completed, the product of the hydrothermal reaction is washed by centrifugation, the detergent is a 0.05 mol / L glacial acetic acid aqueous solution, the speed of each centrifugal washing is 8000 rpm, the time is 3 min, and the number of centrifugal washings is 6 times. The obtained solid is then placed in an oven at 80° C. and dried for 36 h, and manually ground to obtain nano-scale tetragonal barium titanate.
[0074] Example 2
[0075] The difference from Example 1 is that the flow rate of the barium titanium salt solution is 40 mL / min, the flow rate of the sodium hydroxide solution is 40 mL / min, and the molar ratio of sodium hydroxide to the titanium element in the barium titanium salt solution is 6:1; the remaining steps are the same as Example 1.
[0076] Example 3
[0077] The difference from Example 1 is that the flow rates of the barium titanium salt solution and the sodium hydroxide solution are both 20 mL / min, and the remaining steps are the same as Example 1.
[0078] Example 4
[0079] The difference from Example 1 is that the flow rate of the barium titanium salt solution is 70 mL / min, the flow rate of the sodium hydroxide solution is 30 mL / min, the molar ratio of sodium hydroxide to the titanium element in the barium titanium salt solution is 2.5:1, and the remaining steps are the same as Example 1.
[0080] Example 5
[0081] The difference from Example 1 is that the flow rate of the barium titanium salt solution is 30 mL / min, the flow rate of the sodium hydroxide solution is 70 mL / min, the molar ratio of sodium hydroxide to the titanium element in the barium titanium salt solution is 14:1, and the remaining steps are the same as Example 1.
[0082] Example 6
[0083] The difference from Example 1 is that the flow rate of the barium titanium salt solution is 50 mL / min, the flow rate of the sodium hydroxide solution is 50 mL / min, and the remaining steps are the same as Example 1.
[0084] Example 7
[0085] The difference from Example 1 is that the flow rate of the barium titanium salt solution is 50 mL / min, the flow rate of the sodium hydroxide solution is 50 mL / min, the molar ratio of sodium hydroxide to the titanium element in the barium titanium salt solution is 6:1, the temperature of the hydrothermal reaction is 220°C, the time is 48 h, and the remaining steps are the same as Example 1.
[0086] Example 8
[0087] The difference from Example 1 is that the flow rate of the barium titanium salt solution is 50 mL / min, the flow rate of the sodium hydroxide solution is 50 mL / min, the molar ratio of sodium hydroxide to the titanium element in the barium titanium salt solution is 6:1, and the hydrothermal reaction conditions are to place the reactor in an oven at 220°C and carry out the hydrothermal reaction for 72 hours; the remaining steps are the same as Example 1.
[0088] Example 9
[0089] The difference from Example 1 is that the flow rate of the barium titanium salt solution is 50 mL / min, the flow rate of the sodium hydroxide solution is 50 mL / min, the molar ratio of sodium hydroxide to the titanium element in the barium titanium salt solution is 6:1, the temperature of the hydrothermal reaction is 220°C, the time is 96 h, and the remaining steps are the same as Example 1.
[0090] Example 10
[0091] The difference from Example 1 is that the flow rate of the barium titanium salt solution is 50 mL / min, the flow rate of the sodium hydroxide solution is 50 mL / min, the molar ratio of sodium hydroxide to the titanium element in the barium titanium salt solution is 6:1, the temperature of the hydrothermal reaction is 200°C, the time is 36 h, and the remaining steps are the same as Example 1.
[0092] Embodiment 11,
[0093] The difference from Example 1 is that the flow rate of the barium titanium salt solution is 50 mL / min, the flow rate of the sodium hydroxide solution is 50 mL / min, the molar ratio of sodium hydroxide to the titanium element in the barium titanium salt solution is 6:1, the temperature of the hydrothermal reaction is 210°C, the time is 36 h, and the remaining steps are the same as Example 1.
[0094] Comparative Example 1
[0095] The difference from Example 1 is that the barium titanate precursor is obtained by a conventional peristaltic pump neutralization method, and after aging and washing, a hydrothermal reaction is performed at 220° C. for 36 hours to obtain barium titanate nanopowder. The specific preparation steps are as follows:
[0096] 200 mL of sodium hydroxide solution was poured into a three-necked flask and heated to 80° C. in a water bath. 200 mL of the barium titanium salt solution of Example 1 was poured into a beaker and heated to 80° C. in a water bath. The barium titanium salt solution was added to a three-necked flask containing 3 mol / L sodium hydroxide solution at a drip rate of 5 mL / min using a peristaltic pump. The molar ratio of sodium hydroxide to titanium in the barium titanium salt solution was 6:1. At the same time, a stirrer was used to stir at 280 rpm until the barium titanium salt solution was consumed, and then aged for 60 min under the same conditions as in Example 1 to obtain a barium titanate precursor slurry. After precipitation separation and washing, a hydrothermal reaction was carried out under the same conditions as in Example 1.
[0097] Performance Testing
[0098] (1) Figure 1 TEM spectrum and diffraction pattern of the barium titanate precursor in Example 1.
[0099] from Figure 1 It can be seen that the size distribution of the barium titanate precursor is uniform, with an average diameter of 5 nm. The diffraction rings can further determine that the barium titanate precursor is in a polycrystalline form.
[0100] (2) Figure 2 This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 1.
[0101] from Figure 2 As can be seen in the results, the diffraction peak corresponds to BaTiO3 (JCPDS#05-0626), which is a typical tetragonal barium titanate with a crystallinity of 67.78%. The Rietveld method was used to refine the structure and calculate the crystal phase ratio and lattice constant ratio (c / a). The results showed that the tetragonal phase content was 100% and the c / a axis ratio was 1.0071. In addition, the specific surface area of nano-scale tetragonal barium titanate is 14.6824m 2 / g.
[0102] (3) Figure 3 TEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 1, where the scale of (a) is 200 nm and the scale of (b) is 5 nm. Figure 3 It can be seen that the nano-scale tetragonal barium titanate crystals are relatively complete, with no voids or defects inside and good crystal shape.
[0103] (4) Figure 4 This is the SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 1.
[0104] from Figure 4 It can be seen that the average particle size of nano-scale tetragonal barium titanate is 65nm.
[0105] (5) Figure 5 This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 2.
[0106] from Figure 5 It can be seen that the nano-scale tetragonal barium titanate prepared in Example 2 is a typical tetragonal barium titanate with a crystallinity of 68.14%. The structural refinement calculation using the Rietveld method shows that the tetragonal phase content is 100% and the c / a axis ratio is 1.0055.
[0107] (6) Figure 6 This is the SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 2.
[0108] from Figure 6 It can be seen that the average particle size of the nano-scale tetragonal barium titanate prepared in Example 2 is 80 nm.
[0109] (7) Figure 7 This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 3.
[0110] from Figure 7 It can be seen that the nano-scale tetragonal barium titanate prepared in Example 3 is a typical tetragonal barium titanate with a crystallinity of 65.34%. The structural refinement calculation using the Rietveld method shows that the tetragonal phase content is 100% and the c / a axis ratio is 1.0079.
[0111] (8) Figure 8 This is the SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 3.
[0112] from Figure 8 It can be seen that the average particle size of the nano-scale tetragonal barium titanate prepared in Example 3 is 82 nm.
[0113] (9) Fig. 9 This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 4.
[0114] from Fig. 9 It can be seen that the nano-scale tetragonal barium titanate prepared in Example 4 is a typical tetragonal barium titanate with a crystallinity of 68.60%. The structural refinement calculation using the Rietveld method shows that the tetragonal phase content is 100% and the c / a axis ratio is 1.0077.
[0115] (10) Fig.10 This is the SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 4.
[0116] from Fig.10 It can be seen that the average particle size of the nano-scale tetragonal barium titanate prepared in Example 4 is 85 nm.
[0117] (11) Fig.11 This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 5.
[0118] from Fig.11 It can be seen that the nano-scale tetragonal barium titanate prepared in Example 5 is a typical tetragonal barium titanate with a crystallinity of 69.42%. The structural refinement calculation using the Rietveld method shows that the tetragonal phase content is 100% and the c / a axis ratio is 1.0073.
[0119] (12) Fig.12 This is the SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 5.
[0120] from Fig.12 It can be seen that the average particle size of the nano-scale tetragonal barium titanate prepared in Example 5 is 80 nm.
[0121] (13) Fig.13 This is the XRD pattern of the nano-scale tetragonal barium titanate prepared in Example 6.
[0122] from Fig.13 It can be seen that the nano-scale tetragonal barium titanate prepared in Example 6 is a typical tetragonal barium titanate with a crystallinity of 68.51%. The structural refinement calculation using the Rietveld method shows that the tetragonal phase content is 100% and the c / a axis ratio is 1.0076.
[0123] (14) Fig.14 This is the SEM spectrum of the nano-scale tetragonal barium titanate prepared in Example 6.
[0124] from Fig.14 It can be seen that the average particle size of the nano-scale tetragonal barium titanate prepared in Example 6 is 91 nm.
[0125] (15) Fig.15 This is the XRD pattern of barium titanate prepared in Comparative Example 1.
[0126] from Fig.15 It can be seen that the diffraction peak of barium titanate prepared in Comparative Example 1 corresponds to BaTiO3 (JCPDS#31-0174), and the diffraction peak with a 2θ angle between 44° and 46° shows a single peak without obvious splitting, indicating that the nano-barium titanate microcrystals are standard cubic phases. The structural refinement calculation using the Rietveld method shows that the cubic phase content is 100% and the c / a axis ratio is 1.0000.
[0127] (16) Fig.16This is the SEM spectrum of barium titanate prepared in Comparative Example 1.
[0128] from Fig.14 It can be seen that the average particle size of barium titanate prepared in Comparative Example 1 is 96 nm.
[0129] (17) The DLS test results, particle size and crystal information of the barium titanate samples prepared in the embodiment and comparative example are shown in Table 1.
[0130] Table 1 DLS (Span value and D 50 )
[0131]
[0132] It can be seen from Table 1 that the Span value of the nano-scale tetragonal barium titanate prepared in Example 1 is ( Indicates that the span of particle size distribution is 0.7353, and the particle size distribution is in a smaller range. The Span value of the nano-scale tetragonal barium titanate prepared in Example 2 was measured by DLS to be 1.1298. The Span value of the nano-scale tetragonal barium titanate prepared in Example 3 was measured by DLS to be 1.0577. The Span value of the nano-scale tetragonal barium titanate prepared in Example 4 was measured by DLS to be 1.1275. The Span value of the nano-scale tetragonal barium titanate prepared in Example 5 was measured by DLS to be 0.9545. The Span value of the nano-scale tetragonal barium titanate prepared in Example 6 was measured by DLS to be 1.0474. The Span value of the nano-scale tetragonal barium titanate prepared in Example 7 was measured by DLS to be 0.7453. The Span value of the nano-scale tetragonal barium titanate prepared in Example 8 was measured by DLS to be 0.8647. The Span value of the nano-scale tetragonal barium titanate prepared in Example 9 was measured by DLS to be 1.2338. The Span value of the nano-scale tetragonal barium titanate prepared in Example 10 was measured by DLS to be 1.0347. The Span value of the nano-scale tetragonal barium titanate prepared in Example 11 was measured by DLS to be 1.5120. The Span value of the barium titanate prepared in Comparative Example 1 was measured by DLS to be 2.1045, and the particle size distribution range was relatively large. The Span values of the nano-scale tetragonal barium titanate prepared in the present invention are all smaller than those in Comparative Example 1, which shows that the particle size of the nano-scale tetragonal barium titanate prepared in the present invention is more uniform than that of the Comparative Example.
[0133] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing nano-scale tetragonal barium titanate in a confined area, characterized in that: The following steps are involved: The barium titanium salt solution and the precipitant solution are pumped into a mixing reactor of a microchannel reactor for confined mixing, and the obtained mixed slurry is aged to obtain a barium titanate precursor; The flow rates of the barium titanium salt solution and the precipitant solution are independently 20 to 70 mL / min; The barium titanate precursor, the barium source and water are mixed to carry out a hydrothermal reaction to obtain nano-scale tetragonal barium titanate.
2. The confined domain preparation method according to claim 1, characterized in that: The molar ratio of titanium to the precipitant in the barium titanium salt is 1:1-20.
3. The confined domain preparation method according to claim 1 or 2, characterized in that: The precipitant is sodium hydroxide.
4. The confined domain preparation method according to claim 1, characterized in that: The barium titanium salt solution and the precipitant solution enter the mixing reactor through the microchannel of the microchannel reactor; the number of fluid layers in the microchannel is 24 to 60, the thickness of a single fluid layer is 100 μm, and the width of a single fluid layer is 105 μm, 210 μm or 400 μm; the fluid layers of the microchannel are evenly distributed at an injection angle of 30° to form an annular structure, and the center of the annular structure is a circular through hole, namely the mixing reactor.
5. The confined domain preparation method according to claim 4, characterized in that: The cross-sectional area of the single fluid layer is 1.05×10 -2 mm 2 , 2.1×10 -2 mm 2 or 4.0×10 -2 mm 2 .
6. The confined domain preparation method according to claim 1, characterized in that: Before the limited mixing, the method further includes: preheating the barium titanium salt solution and the precipitant solution; the preheating temperature is 70-80°C.
7. The confined domain preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 200-250° C., and the insulation time is 24-100 hours.
8. The confined domain preparation method according to claim 1, characterized in that: The molar ratio of barium in the barium source to titanium in the barium titanate precursor is 1 to 3:
1.
9. The confined domain preparation method according to claim 1, characterized in that: The aging temperature is 70-80° C., and the insulation time is 30-60 minutes.
10. The nano-scale tetragonal barium titanate prepared by the confined preparation method according to any one of claims 1 to 9, characterized in that: The nano-scale tetragonal barium titanate has an average particle size of ≤100 nm, a crystallinity of ≥65%, and a tetragonal phase content of 100%.
Citation Information
Cited By
Preparation method of barium titanate powder
CN120922913A
Nanometer tetragonal-phase barium titanate and process strengthening continuous preparation method thereof
CN122324847A